Validated stability-indicating HPLC-DAD method for determination of the phosphodiesterase (PDE-4) inhibitor roflumilast - Tarek S. Belal; Hytham M. Ahmed; Mohamed S. Mahrous; Hoda G. Daabees; Mostafa M. Baker (Faculty of Pharmacy, Cairo University, 2014)
A comprehensive stability indicating HPLC with diode array detection method was developed for determination of the recently approved phosphodiesterase type 4 (PDE-4) inhibitor roflumilast (RFL). Effective chromatographic separation was achieved using Durashell C18 column (4.6 × 250 mm, 5 μm particle size) with isocratic elution of the mobile phase composed of 0.0065 M ammonium acetate pH 6.3, methanol and acetonitrile in the ratio of 30:35:35 (by volume). The mobile phase was pumped at a flow rate of 1.3 mL/min, and quantification of RFL was based on measuring its peak areas at 251 nm. RFL eluted at retention time 6.2 min. Analytical performance of the proposed HPLC procedure was thoroughly validated with respect to system suitability, linearity, range, precision, accuracy, specificity, robustness, detection and quantification limits. The linearity range was 2.5-200 μg/mL with correlation coefficient >0.9998. The drug was subjected to stress conditions of neutral, acidic and alkaline hydrolysis, oxidation, photolysis and thermal degradation. The proposed method proved to be stability-indicating by resolution of the drug from its forced degradation products. Moreover, specificity of the method was verified by resolution of drug from more than 20 pharmaceutical compounds of various medicinal categories. The validated HPLC method was successfully applied to the analysis of the cited drug in its tablet dosage form. The proposed method made use of DAD as a tool for peak identity and purity confirmation.